Case Studies in Bayesian Statistical Modelling and Analysis by ALSTON, C.L., MENGERSEN, K.L. and PETTITT, A.N. Issue 3 (23rd September 2013) - Lee, Jaeyong
Abstract EDITOR: TAESUNG PARK Case Studies in Bayesian Statistical Modelling and Analysis (C.L. Alston, K.L. Mengersen, and A.N. Pettitt) Jaeyong Lee Generalized Estimating Equations (2nd ed.) (James W. Hardin and Joseph M. Gibe) Woncheol Jang Spatio‐Temporal Design: Advances in Efficient Data Acquisition (Jorge Mateu and Werner G. Müller) Johan Lim Handbook of Markov Chain Monte Carlo (S. Brooks, A. Gelman, G. L. Jones, and X. Meng) Hedibert Freitas Lopes